2020
DOI: 10.1111/cod.13601
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term skin reactions following use of N95 respirators and medical masks

Abstract: Background: In the context of the COVID-19 pandemic, cases of adverse skin reactions related to masks have been observed. Objective:To analyze the short-term effects of N95 respirators and medical masks, respectively, on skin physiological properties and to report adverse skin reactions caused by the equipment.Methods: This study used a randomized crossover design with repeated measurements. Twenty healthy Chinese volunteers were recruited. Skin parameters were measured on areas covered by the respective mask … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
4
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(205 citation statements)
references
References 25 publications
8
168
4
12
Order By: Relevance
“…More importantly, many laboratory studies fail to account for crucial clinical and behavioral factors. For example, studies have reported lower adherence to N95 respirators compared to medical masks, due to higher rates of adverse events (35,36,49). In one study on the tolerability of respirators in HCWs, the probability of discontinuing respirator use during an 8-h work shift was around 50 to 70%, despite regular 15-or 30-min breaks every 2 h (50).…”
Section: Laboratory Studies On Masksmentioning
confidence: 99%
“…More importantly, many laboratory studies fail to account for crucial clinical and behavioral factors. For example, studies have reported lower adherence to N95 respirators compared to medical masks, due to higher rates of adverse events (35,36,49). In one study on the tolerability of respirators in HCWs, the probability of discontinuing respirator use during an 8-h work shift was around 50 to 70%, despite regular 15-or 30-min breaks every 2 h (50).…”
Section: Laboratory Studies On Masksmentioning
confidence: 99%
“…Of note, worsening of preexisting facial skin problems such as acne or rosacea was frequently reported. 2 This scenario is certainly similar to what the health care personnel is suffering nowadays in Europe. 3 The identification of these cutaneous reactions, how to prevent and treat them is the objective of this document.…”
Section: European Task Force On Contact Dermatitis Statement On Coronmentioning
confidence: 63%
“…It might relate to the shortage of masks and goods in supermarkets and pharmacies in China in February [ 28 ]. What is more, some preventive behavior, such as wearing masks, might be relatively difficult to perform due to discomfort, inconvenience, and adverse skin reactions [ 42 ].…”
Section: Discussionmentioning
confidence: 99%